Appraisal of BEP (2004-2009): towards deepening partnership with the government of Bangladesh - Kassam, Yusuf; Raynor, Janet; Ryan, Anne; Wirak, Anders (© BRAC, 2016)
This appraisal prepared for BRAC Donor Liaison Office, September 4, 2003